-9y+42=4y-36

Simple and best practice solution for -9y+42=4y-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9y+42=4y-36 equation:



-9y+42=4y-36
We move all terms to the left:
-9y+42-(4y-36)=0
We get rid of parentheses
-9y-4y+36+42=0
We add all the numbers together, and all the variables
-13y+78=0
We move all terms containing y to the left, all other terms to the right
-13y=-78
y=-78/-13
y=+6

See similar equations:

| 9+4(x=1)=25 | | |x−12|=−3x | | -a-2-2a=-8 | | x*3-15=27 | | 4=7k-3k | | 7/2z+5=9/4z+6 | | 1-3x+15=2÷(5x-12) | | x(4+12)=36 | | x/5-12=-3 | | ½(6-x)x=½(6x-x2)=3x-½x2 | | -4(2r+r+6)=0 | | x/3-15=27 | | 83+(5y+2)=180 | | 7/2b+5=9/4b+6 | | 4x+2^5=3*2x+2 | | 1/6a-3/8=0 | | 1/7a-3/8=0 | | 2x+2x-5+2x-5=38 | | 22=-x-6 | | -17.4+0.3s=7.8s+9.48-3.3s | | 1-4-x-(4-1)=x-2+4 | | 1/7c+3/4=9/8 | | (x+8)^2=15 | | -12-s=20+15s | | 8x-3=3x+3 | | 12(x−13)=13(12−x) | | 20+3b=8b | | 4x+2*(x+3)=2*(x+2) | | (5v^2)+10v+33=-5 | | 9x-6*3x+81=0 | | |z+59|=|z−79| | | 2+(x(x))-(-2x)=x-2-(-x(-x)) |

Equations solver categories